Electric field-induced critical demixing in lipid bilayer membranes - Groves, Jay T. (The National Academy of Sciences, 1998)
Electric fields can induce lateral reorganization of lipids in fluid bilayer membranes. The resulting concentration profiles readily are observed in planar-supported bilayers by epifluorescence microscopy. When a fluorescently labeled lipid was used to probe the field-induced separation of cardiolipin from egg-phosphatidylcholine, an enhanced sensitivity to the electric field was observed that is attributed to a critical demixing effect. A thermodynamic model of the system was used to analyze the results. The observed concentration profiles can be understood if the lipid mixture has a critical temperature equal to 75°K. The steady-state distribution of lipids under the influence of an electric field is very sensitive to demixing effects, even at temperatures well above the critical temperature for spontaneous phase separation, and this may have significant consequences for organization and structural changes in natural cell membranes.